Immunogenicity and lot-to-lot consistency of a ready to use liquid bovine-human reassortant pentavalent rotavirus vaccine (ROTASIIL - Liquid) in Indian infants. Issue 19 (1st May 2019) - Kawade, Anand; Babji, Sudhir; Kamath, Veena; Raut, Abhishek; Kumar, Chandra Mohan; Kundu, Ritabrata; Venkatramanan, Padmasani; Lalwani, Sanjay K.; Bavdekar, Ashish; Juvekar, Sanjay; Dayma, Girish; Patil, Rakesh; et al.
Abstract: Background: A lyophilized bovine-human rotavirus reassortant pentavalent vaccine (BRV-PV, Rotasiil®) was licensed in 2016. A liquid formulation of this vaccine (LBRV-PV, Rotasiil - Liquid) was subsequently developed and was tested for non-inferiority to Rotasiil® and for lot-to-lot consistency. Methods: This Phase II/III, open label, randomized study was conducted at seven sites across India from November 2017 to June 2018. Participants were randomized into four arms; Lots A, B, and C of LBRV-PV and Rotasiil® in 1:1:1:1 ratio. Three doses of study vaccines were given at 6, 10, and 14 weeks of age. Blood samples were collected four weeks after the third dose to assess rotavirus IgA antibody levels. Non-inferiority of LBRV-PV to Rotasiil was proven if the lower limit two-sided 95% confidence interval (CI) of geometric mean concentration (GMC) ratio was at least 0.5. Lot-to-lot consistency was proven if 95% CI of the GMC ratios of three lots were between 0.5 and 2. Solicited reactions were collected by using diary cards. Results: Of the 1500 randomized infants, 1436 infants completed the study. The IgA GMC ratio of LBRV-PV to Rotasiil® was 1.19 (95% CI 0.96, 1.48). The corresponding IgA seropositivity rates were 60.41% (57.41, 63.35) and 52.75% (47.48, 57.97). The IgA GMC ratios among the three LBRV-PV lots were: Lot A versus Lot B: 1.34 (1.03, 1.75); Lot A versus Lot C: 1.22 (0.93, 1.60); and Lot B versus Lot C: 0.91 (0.69, 1.19). The 95% CIs for the GMC ratios were between 0.69 and 1.75. The incidence of solicited reactions was comparable across the four arms. Only one serious adverse event of gastroenteritis event in the Rotasiil® group was causally related. Conclusion: The immunological non-inferiority of LBRV-PV against Rotasiil® as well as lot-to-lot consistency of LBRV-PV was demonstrated. LBRV-PV had safety profile similar to Rotasiil®. Trial registration number : Clinical Trials.Gov [NCT03474055] and Clinical Trial Registry of India [CTRI/2017/10/010104].